2018
DOI: 10.1007/s00204-018-2335-4
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor α attenuates high-cholesterol diet-induced toxicity and pro-thrombotic effects in mice

Abstract: Peroxisome proliferator-activated receptor α (PPARα) is involved in the regulation of fatty acid and cholesterol metabolism. A high-cholesterol (HC) diet increases the risk of developing cardiovascular diseases (CVD); however, it is unclear whether the toxic effects of cholesterol involve changes in thrombotic factor expression, and whether PPARα is necessary for such effects. To investigate this possibility, we fed a HC diet to wild-type (WT) and Ppara-null mice and measured cholesterol and triglyceride conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…These data add to growing evidence that PPARα contributes to the regulation of coagulation factor synthesis. A recent study found that deletion of PPARα worsens the prothrombotic effect of a high‐cholesterol diet through increased synthesis of several coagulation factors, ( 32 ) and earlier work illustrates that PPARα decreases fibrinogen‐β expression by directly binding to a DNA response element and interfering with a transcriptional coactivator complex. ( 33 ) Indeed, one might speculate that decreasing coagulation factor synthesis thereby reducing thrombotic potential could contribute to some of the benefits of fibrates in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These data add to growing evidence that PPARα contributes to the regulation of coagulation factor synthesis. A recent study found that deletion of PPARα worsens the prothrombotic effect of a high‐cholesterol diet through increased synthesis of several coagulation factors, ( 32 ) and earlier work illustrates that PPARα decreases fibrinogen‐β expression by directly binding to a DNA response element and interfering with a transcriptional coactivator complex. ( 33 ) Indeed, one might speculate that decreasing coagulation factor synthesis thereby reducing thrombotic potential could contribute to some of the benefits of fibrates in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…And PGC-1a acts as a key regulator of mitochondrial biogenesis and function, PPARa is involved in regulating fatty acid and cholesterol metabolism, and CPT 1A is an enzyme that is anchored to the outer mitochondrial membrane (OMM), and it regulates the passage of fatty acids into the mitochondria and interferes with boxidation of long-chain fatty acids. These three factors play an important role in the occurrence of fatty acid oxidation (38)(39)(40). So, these three factors were tested and shown in Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…PPARA and PPARG ligands, known as peroxisome proliferators, have been shown to induce cell cycle arrest at the G1 phase of the cell cycle to prompt the differentiation of liposarcoma, colon, prostate and BC cells, conferring a less malignant phenotype to the cells [28]. PPARA and PPARG are also involved in the regulation of cholesterol metabolism [48], which was shown to regulate cell adhesion in breast cancer cell lines [49].…”
Section: Discussionmentioning
confidence: 99%